Evaluation of Chemokine Ligand 4 and Matrix Metalloproteinase-2 as Inflammatory Biomarkers in the Serum of Patients with Cataracts - Ali, Nooruldeen; Nazar Ibraheim, Wijdan; Hasan Jaaz, Muataz (University of Thi-Qar Journal of Science, 2025)
Cataracts are a progressive health issue with significant implications for individuals and public health systems.  They are considered a critical global health issue, particularly affecting older adults. MMP-2 and CCL4 are both chemokines that are known to play a critical role in inflammation and tissue remodeling. The collected data were analysed by using SPSS and visualization tools.  Our results indicate a significant correlation between MMP-2 and CCL4 among cataract patients.  There is a substantial relationship between MMP-2 and other factors, such as gender and residency state, unlike CCL4. No significant correlation exists between the two serum biomarkers (MMP-2 and CCL4) and smoking cataract patients. By exploring the expression of MMP-2 and CCL4, this study aims to enhance cataract pathophysiology and identify inflammatory biomarkers associated with cataract progression. measuring serum levels of MMP-2 and CCL4 in cataract patients to assess their role in tissue remodeling, inflammation, and post-operative complications.